Variability in Early Ahmarian lithic technology and its implications for the model of a Levantine origin of the Protoaurignacian. Issue 82 (May 2015) - Kadowaki, Seiji; Omori, Takayuki; Nishiaki, Yoshihiro
Abstract: This paper re-examines lithic technological variability of the Early Ahmarian, one of the early Upper Palaeolithic cultural entities in the Levant, which has often been regarded as a precursor of the Protoaurignacian (the early Upper Palaeolithic in Europe) in arguments for the occurrence of a cultural spread in association with the dispersal of Homo sapiens from the Levant to Europe. Using quantitative data on several lithic techno-typological attributes, we demonstrate that there is a significant degree of variability in the Early Ahmarian between the northern and southern Levant, as previously pointed out by several researchers. In addition, we suggest that the technology similar to the southern Early Ahmarian also existed in the northern Levant, i.e., the Ksar Akil Phase 4 group (the KA 4 group), by introducing new Upper Palaeolithic assemblages from Wadi Kharar 16R, inland Syria. We then review currently available stratigraphic records and radiocarbon dates (including a new date from Wadi Kharar 16R), with special attention to their methodological background. As a result, we propose alternative chronological scenarios, including one that postulates that the southern Early Ahmarian and the KA 4 group appeared later than the northern Early Ahmarian with little or no overlap. On the basis of the alternative scenarios of chronological/geographical patterns of the Early Ahmarian variability, we propose four possible relationships between the Protoaurignacian and the Early Ahmarian, including a new scenario that the appearance of the Protoaurignacian preceded those of similar technological entities in the Levant, i.e., the southern Early Ahmarian and the KA 4 group. If the last hypothesis is substantiated, it requires us to reconsider the model of a Levantine origin of the Protoaurignacian and its palaeoanthropological implications.